Feminist frontiers - Rupp, Leila J. , 1950-; Taylor, Verta A.; Whittier, Nancy , 1966- (McGraw-Hill, 2012)
An anthology of feminist writings. It offers analyses of the causes and consequences of gender inequality in interaction with race, ethnicity, class, sexuality, ability, and nation, and introduces students to feminist theory and methodology